Rekonstruksi Perilaku Etik Hakim dalam Menangani Perkara Berbasis Hukum Progresif* - M. Syamsudin (Fakultas Hukum Universitas Islam Indonesia, 2011)
The research problem is on how existing condition of ethical behavior if judge in handling cases in court and reconstruction of ethical behavior of judge based on progressive law. This research included in non-doctrinal legal research tradition through sociological approach. The data collected through interview, observation, and document study which is analyzed through interactive model from Mattew B. Miles and A. Michael Haberman. Data validation is conducted through source and method triangulation.The research result shows that judge behavior in handling case in court is influenced by orientation value adopted by the judge. Orientation value carved in the soul and psychological realm of the judge significantly determines judge’s orientation in handling case. Judge will choose values based on prioritized matters in life. Fact shows that there are three types of judge’s orientation in handling case which are material oriented judge (materialist), benefit oriented judge (pragmatic) and ideal law oriented judge (idealist).